Effect of baseline disease severity on achievement of treatment target with apremilast: results from a pooled analysis. (23rd August 2021) - Reich, K.; Mrowietz, U.; Menter, A.; Griffiths, C.E.M.; Bagel, J.; Strober, B.; Nunez Gomez, N.; Shi, R.; Guerette, B.; Lebwohl, M.
Abstract: Background: Treating to absolute treatment targets rather than relative measures such as Psoriasis Area and Severity Index (PASI)‐75 is emerging as an important clinical concept included in psoriasis guidelines and clinical practice. Achieving treatment targets is associated with achievement of long‐term outcomes. Objective: To evaluate the relationship between psoriasis severity, disease characteristics and achievement of PASI ≤2 with apremilast in a pooled analysis of the phase 3 ESTEEM 1 and 2 (NCT01194219 and NCT01232283), phase 3b LIBERATE (NCT01690299) and phase 4 UNVEIL (NCT02425826) clinical trials. Methods: Pooled data from patients with moderate‐to‐severe plaque psoriasis randomized to apremilast 30 mg BID were analysed by baseline PASI quartiles (Q1: 2.4–13.1; Q2: 13.2–15.9; Q3: 16.0–20.0; Q4: 20.1–57.8). Assessments included PASI, Dermatology Life Quality Index (DLQI), Scalp Physician's Global Assessment (ScPGA; ScPGA ≥1) and target (worst) Nail Psoriasis Severity Index (NAPSI; NAPSI ≥1). Results: Of 1062 patients, 963 had ScPGA ≥1 and 643 had NAPSI ≥1; 771 patients with baseline and Week 32 PASI assessments were included in analyses of Week 32 PASI target achievement. Rates of PASI ≤2 at Week 32 were greater in lower PASI quartiles (Q1: 43.5%; Q2: 31.2%; Q3: 26.8%; Q4: 18.4%). Most patients achieving PASI ≤2 target (83.6%) achieved DLQI ≤5 at Week 32; 59.3% of patients who did not achieve PASI ≤2 target achieved DLQI ≤5. At Week 32, mean improvements in ScPGA and NAPSI were similar with more moderate vs. more severe disease (ScPGA, range: 1.1–1.4; NAPSI, range: 1.6–2.5). In a subgroup analysis, achievement of PASI ≤2 target was higher in the lowest PASI quartile and with disease duration <5 years. Conclusions: Greater achievement of PASI ≤2 was observed in patients with more moderate vs. more severe skin disease. Apremilast may be particularly beneficial in more moderate disease early in the treatment paradigm.